Analysis of internal cooling system in a vented cavity using P, PI, PID controllers - Md. Shahneoug Shuvo; Fardin Ishtiaq; Tousif Jamee; Jayanto Das; Sumon Saha (Results in Engineering, 2022)
The investigation of the problem of internal cooling system inside a vented cavity utilizing P, PI, and PID controllers are carried out in this paper. The cavity consists of an outlet, an airflow inlet, a temperature sensor, and an isothermal heat source. The remaining walls are kept at ambient temperature. A temperature probe at a central location is used to measure the internal cooling condition and hence, to control the inlet air velocity via three different types of controller arrangements. The governing Navier-Stokes and energy equations along with appropriate boundary conditions are solved using Galerkin finite element technique. Parametric simulation is conducted by considering different values of proportional (0.01, 0.05, 0.1 ms−1K−1), integral (0.1, 0.2, 0.5 ms−2K−1), and derivative (0.001, 0.0001, 0.00001 mK−1) gains for three different types of controllers. The velocity and temperature contours are used to visualize the thermo-fluid behaviors of airflow inside the cavity. Besides, non-dimensional fluid temperature of the cavity at the set point is monitored closely to determine and compare the performance of the controllers.